2019
DOI: 10.3748/wjg.v25.i23.2846
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytochrome P450 polymorphisms and functions in development of ulcerative colitis

Abstract: Cytochromes P450s (CYPs) are terminal enzymes in CYP dependent monooxygenases, which constitute a superfamily of enzymes catalysing the metabolism of both endogenous and exogenous substances. One of their main tasks is to facilitate the excretion of these substances and eliminate their toxicities in most phase 1 reactions. Endogenous substrates of CYPs include steroids, bile acids, eicosanoids, cholesterol, vitamin D and neurotransmitters. About 80% of currently used drugs and environmental chemicals comprise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 159 publications
2
13
0
Order By: Relevance
“…steroids) and exogenous (e.g. drugs) substances (59), was lower in the colonic enterocytes of patients suffering from Crohn's disease and ulcerative colitis (60). Our observation on Atlantic salmon also corroborates with this finding.…”
Section: Soy Products Also Impaired the Transport Mechanisms And Metasupporting
confidence: 88%
“…steroids) and exogenous (e.g. drugs) substances (59), was lower in the colonic enterocytes of patients suffering from Crohn's disease and ulcerative colitis (60). Our observation on Atlantic salmon also corroborates with this finding.…”
Section: Soy Products Also Impaired the Transport Mechanisms And Metasupporting
confidence: 88%
“…Given that ulcerative colitis begins most commonly between the ages of 15 and 25 with a second peak of onset in the 6th decade of life, Mother's reported symptoms are concordant with her ulcerative colitis / bowel disease susceptibility. We also note that according to Sen and Stark ( 2019 ), CYP2D6 * 4 polymorphisms may be risk factors for ulcerative colitis. Both Mother and Daughter display CYP2D6 * 4 .…”
Section: Discussionsupporting
confidence: 55%
“…[91,92] Studies have shown that induction of colonic CYP27B1, enhancing the local production of 1,25(OH) 2 D 3 , is a protective mechanism for colonic inflammation. [93,94] Collectively, these data suggest that MCh may exert its anti-inflammatory action through inducing the production of 1,25(OH) 2 D 3 so as to protect the mucosal barrier and decrease colonic inflammation , though it might be an exaggerated inference but highly probable in the light of current literature. Further studies are required for a better understanding of the role of either CYP27B1 or 1,25(OH) 2 D 3 in the pathogenesis of UC.…”
Section: Discussionmentioning
confidence: 87%